Phytoplankton functional groups in a tropical reservoir in the Brazilian semiarid region - Lins, Ruceline Paiva Melo; Ovruski de Ceballos, Beatriz Susana; Serramo Lopez, Luiz Carlos; Gomes Barbosa, Luciana (Revista de Biología Tropical, 2017)
Phytoplankton functional groups structure and species abundance vary according to environmental conditions. The present study investigated the natural and anthropogenic stressors that affect phytoplankton functional group biomass in a Brazilian semiarid region reservoir (Argemiro de Figueiredo reservoir). Sampling occurred between August 2007 and July 2009 on a bi-monthly basis for the first year, and in a monthly basis for the last two years. There were three collection points (PC: river confluence; PNC: near the cages; PD: dam site). The water environment analysis of abiotic variables included: temperature, transparency, coefficient of vertical light attenuation, dissolved oxygen, pH, electrical conductivity, alkalinity, dissolved inorganic nitrogen, and reactive soluble phosphorus. Phytoplankton samples were collected into a Van Dorn bottle, and were then preserved in acetic lugol and were quantified using an inverted microscope to determine phytoplankton density and biomass; the identified species were assembled in functional groups. The data were explored by canonical correspondence analysis. Individual analyses were made to test the temporal and spatial variability of the data and the factors that interfered most with the biotic and abiotic variables. Functional groups S1, SN, and K, consisting of filamentous Planktothrix agardhii (Gomont) Anagnostidis & Komárek, Cylindrospermopsis raciborskii (Woloszynska) Seenaya & Subba Raju, and the coccoid Aphanocapsa incerta (Lemmermann) Cronberg & Komárek, respectively, dominated the dry months when the water was warm, turbid, and alkaline. The overflow reservoir served as a natural disturbance reducing the phytoplankton biomass to less than 50 % and the dominance of cyanobacteria, promoting the domain of functional groups F, M, MP, Lo, and X2. The nutrient inputs from intensive fish farming, associated with a low local depth (Zmax = 7.7 m) close to the cages (PNC), resulted in a significant human disturbance that increased the prevalence of functional groups S1, SN, and K, which are composed primarily of cyanobacteria. We concluded that, in reservoirs, overflow events are natural disturbances that have the ability to reduce phytoplankton biomass and alter the structure of local communities, and that intensive fish farming is an anthropogenic disturbance that increases the availability of nutrients and stimulates an increase in biomass of the functional groups that include cyanobacteria. Furthermore, the functional groups of phytoplankton were reliable control of environmental conditions in the reservoirs of tropical semiarid regions.